An Explorative Investigation of Referee Abuse in English Rugby League - Tom Webb; Mike Rayner; Richard Thelwell (Journal of Applied Sports Management, 2018)
This article explored the experiences of 89 rugby league referees in England who undertook a mixed methods online survey from the January 9 to March 31, 2017. The results of the survey produced rich data from the open responses, and the quantitative measures are used to support these open responses. Findings identified an established culture of abuse towards referees, a refereeing workforce requiring greater support, better communication with the governing body and, therefore, revisions to existing policy and training. Conclusions identified specific recommendations and policy implications to improve the operational environment and working conditions and increased support for referees. Subscribe to JASM
Keywords: Referees; abuse; operational environment; working conditions; rugby league